2005
DOI: 10.1063/1.2001158
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of surface roughness scattering in silicon nanowire transistors

Abstract: In this letter, we report a three-dimensional (3D) quantum mechanical simulation to investigate the effects of surface roughness scattering (SRS) on the device characteristics of Si nanowire transistors (SNWTs). We treat the microscopic structure of the Si/SiO 2 interface roughness directly by using a 3D finite element technique. The results show that 1) SRS reduces the electron density of states in the channel, which increases the SNWT threshold voltage, and 2) the SRS in SNWTs becomes more effective when mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 14 publications
4
106
0
Order By: Relevance
“…The electron density is used to calculate, self-consistently, the electrostatic potential through the Poisson's equation. The obtained solutions of the NEGF and Poisson equations are iterated in a Gummel-like loop until density and current converge [10][11][12].…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The electron density is used to calculate, self-consistently, the electrostatic potential through the Poisson's equation. The obtained solutions of the NEGF and Poisson equations are iterated in a Gummel-like loop until density and current converge [10][11][12].…”
Section: Simulation Methodologymentioning
confidence: 99%
“…11,22 In these devices it is observed that surface roughness and channel shape can strongly affect device performance. 23 A highly isotropic, chemically driven etch is required for this undercut and, because the channel is exposed, it must have extremely high selectivity for the buffer relative to the channel. At very small dimensions below the gate wet etching can encounter challenges with the reliability of the etch due to limited flow in tight spaces affecting etchant diffusion as well as released channel collapse or incomplete etchant removal due to capillary force from an aqueous cleaning solution.…”
Section: Potential Applications For Atomic Layer Etchingmentioning
confidence: 99%
“…[4] For doped Si NW with radius of 5-60 nm the resistivity increased due to change in the impurity activation energy by the quantum confinement effects. [18] In our case, for the undoped NW with a cross section of 2020 nm 2 , reduction of width by ultrathin oxide is less than 1 nm, therefore, such effect is insignificant.…”
Section: Current Calculationsmentioning
confidence: 99%
“…Of particular attention is the role of surface and interface properties in carrier transport in advanced Si nanowire (NW) devices. [1][2][3][4] Scanning probe techniques such as scanning spreading resistance microscopy (SSRM), scanning Kelvin probe microscopy (SKPM) have been employed for two-dimensional (2D) characterization of modern devices. However, high load from the SSRM probe and the series resistance have become the limitation for quantitative characterization of nanowire devices smaller than 50 nm.…”
Section: Introductionmentioning
confidence: 99%